Work from Home & Productivity: Evidence from Personnel & Analytics Data on IT Professionals - Michael Gibbs; Friederike Mengel; Christoph Siemroth (Institute of Labor Economics (IZA), 2021)
Using personnel and analytics data from over 10,000 skilled professionals at a large Asian IT services company, we compare productivity before and during the work from home [WFH] period of the Covid-19 pandemic. Total hours worked increased by roughly 30%, including a rise of 18% in working after normal business hours. Average output did not significantly change. Therefore, productivity fell by about 20%. Time spent on coordination activities and meetings increased, but uninterrupted work hours shrank considerably. Employees also spent less time networking, and received less coaching and 1:1 meetings with supervisors. These findings suggest that communication and coordination costs increased substantially during WFH, and constituted an important source of the decline in productivity. Employees with children living at home increased hours worked more than those without children at home, and suffered a bigger decline in productivity than those without children.
Keywords: D2; M5; 330; working from home; telecommuting; remote working; productivity; pandemic; COVID-19; collaboration; work hours; work time